2011
DOI: 10.1016/j.infbeh.2010.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Information processing efficiency and regulation at five months

Abstract: Infants with short look durations are generally thought to have better attentional capabilities due to their efficient information processing. Although effortful attention is considered a key component of developing regulatory abilities, little is known about the relation between speed and efficiency of processing and self-regulation. In this study, 5-month-old infants with shorter look duration had greater EEG power values than infants with longer look during baseline, as well as during a distressing task and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…This baseline procedure quiets the infant, yields minimal eye and gross motor movements, and allows the infant to tolerate the EEG cap (e.g. Bell, 2001, 2012; Diaz & Bell, 2011; Fox, Henderson, Rubin, Calkins & Schmidt, 2001). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This baseline procedure quiets the infant, yields minimal eye and gross motor movements, and allows the infant to tolerate the EEG cap (e.g. Bell, 2001, 2012; Diaz & Bell, 2011; Fox, Henderson, Rubin, Calkins & Schmidt, 2001). …”
Section: Methodsmentioning
confidence: 99%
“…Other infant work has demonstrated that larger baseline and task specific 6–9 Hz EEG power values at frontal locations are associated with better performance on an attention task (Diaz & Bell, 2011) and on working memory tasks that rely on attention shifting (e.g., Bell, 2002; Bell & Wolfe, 2007; Cuevas & Bell, 2011). Taken together, these results suggest that neural activity within the frontal cortex may play a particularly important role in the development of infants’ observed attention behavior.…”
Section: Neurophysiological Underpinnings Of Attention Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Others have also found that distraction strategies, in which children shift their attention away from the source of arousal and orient toward a more positive or neutral stimulus, may assist the child in managing early frustration and fear responses (Calkins, Smith, Gill & Johnson, 1998; Diaz & Bell, 2011; Stifter & Braungart, 1995). Indeed, much research, including contingency studies, has demonstrated that infants who avert their gaze or distract away from a distressing stimulus (i.e., frustrating or fearful) show reduced negative affect in the moment, and less anxious behavior over time (Crockenberg & Leerkes, 2004, 2006; Stifter & Spinrad, 2002).…”
Section: Emotion Regulation and Attentional Abilitiesmentioning
confidence: 99%
“…Some of our initial findings show associations between attentional processing measures of looking time, emotion regulation skills during distress, and frontal EEG activity (Diaz & Bell, 2009). Specifically, 5-month-old infants who process information quickly (i.e., are short lookers during familiarization of a stimulus, as opposed to long lookers; Colombo, Mitchell, Coldren, & Freeseman, 1991), appear less distressed during the arm restraint task, as indicated by behaviors and frontal EEG activity during the task.…”
Section: Conceptual Framework For Emotion-cognition Integrationmentioning
confidence: 96%